The role of conventional and molecular cytogenetics in the diagnosis of microdeletion syndromes - Salwati Shuib; Sharifah Noor Akmal; Zarina Abdul Latif; Zubaidah Zakaria; Nor Zarina Zainal Abidin (Penerbit UKM, 2006)
In this report we demonstrate the role of fluorescence in situ hybridisation (FISH) and conventional cytogenetic methods in clinically and cytogenetically confirmed cases of microdeletion syndromes. A total of nine cases were referred to the Cytopathology and Cytogenetic Unit, Hospital Universiti Kebangsaan Malaysia (HUKM) from 2002 to 2004. They include three Prader-Willi syndrome, three DiGeorge syndrome, one Williams syndrome, one Miller-Dieker syndrome and one Kallmann syndrome. Blood samples from the patients were cultured and harvested following standard procedures. Twenty metaphases were analysed for each of the cases. FISH analysis was carried out for all the cases using commercial probes (Vysis, USA): SNRPN and D15S10 for Prader-Willi syndrome, LIS1 for Miller Dieker syndrome, ELN for Williams syndrome, KAL for Kallmann syndrome, TUPLE 1 and D22S75 for DiGeorge syndrome. Conventional cytogenetic analysis revealed normal karyotypes in all but one case with structural abnormality involving chromosomes 9 and 22. FISH analysis showed microdeletions in all of the nine cases studied. This study has accomplished two important findings ie. while the FISH method is mandatory in ruling out microdeletion syndromes, conventional cytogenetics acts as a screening tool in revealing other chromosomal abnormalities that may be involved with the disease